Enterprise Architecture Design Using TOGAF ADM at Apotek Kimia Farma - Ilham Abu; Nurul Azizah; Andika Isma (Indonesian Journal of Enterprise Architecture, 2023)
Information technology is developing quite rapidly and has a significant impact in various aspects of business, including in the pharmaceutical industry. This research aims to design enterprise architecture at Apotek Kimia Farma. The method used in this research is TOGAF ADM (The Open Group Architecture Framework Architecture Development Method), which consists of several phases, namely preliminary phase, architecture vision, business architecture, information system architecture, technology architecture, opportunities and solutions, and migration planning. This research will produce a blueprint of enterprise architecture design that is in accordance with the needs and objectives of the Apotek Kimia Farma. This blueprint includes structured guidance on architecture components such as business architecture, information system architecture, and technology architecture. By having this blueprint, Apotek Kimia Farma can have clear guidelines in optimizing the use of information technology, increasing operational efficiency, and strengthening its competitive advantage in the pharmaceutical industry. The results of this research are expected to provide significant benefits to Apotek Kimia Farma and the pharmaceutical industry in general. A structured and integrated enterprise architecture design will help Apotek Kimia Farma in facing technological challenges and increasingly fierce competition.